PENGARUH SHOPPING LIFESTYLE,FASHIONINVOLVEMENT,PRE-DECISION STAGE,POST-DECISION STAGE DAN INSTORE ENVIRONMENT TERHADAP IMPULSE BUYING DI STROBERI STORE - VC, Ivan (Kajian Ilmiah Mahasiswa Manajemen, 2012)
The purpose of this research is to identify the impact of shopping lifestyle, fashion involvement, shopping pre-decision stage, post-decision stage, and instore shopping environment towards impulse buying konsumen at Strawberry Store. The Strawberry Store is the choosen object cause the retailer innovative at fashion which offering to the consumer. The type of this research is causal. The independent variables are: shopping lifestyle, fashion involvement, shopping pre-decision stage, post-decision stage, and instore shopping environment, the dependent variable is impulse buying. The number of samples are 200 samples. Data technique analysis is multiple regression. The result of this research showing that shopping lifestyle, fashion involvement, shopping pre-decision stage, post-decision stage, and instore shopping environment have influenced towards impulse buying at Strawberry Store. The impact all of this variables are 78%.